Influences of the back plate on competitive swimming starting motion in particular projection skill - Nomura, T.; Takeda, T.; Takagi, H. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: For the swimming, an important factor is motion on the block to start fast. The starting platform with a back plate has been approved by FINA. The purpose of this study was to identify the influences of the back plate to swimming starting motion in particular projection skill. METHODS: Ten male college swimmers were used as subjects. They performed the track start from the conventional platform (CON) and from the platform with the back plate (BKP). The back plate was used a pedal for a track and field starting equipment. Digital video camera was used to record the performance of each trial from side view. The projective motion was divided into set position, acceleration phase, take-off and flight phase. Kinematic variables were calculated using 2D-DLT method. These variables for the projective motion consisted of the 15 items. RESULTS: At the set position, the horizontal coordinates of CM were BKP;-0.205 (0.054) m, CON;-0.253 (0.054) m. The CM position of BKP was significantly forwarder. The knee angles of rear leg were respectively BKP;84.3 (11.3) degree, CON;97.1 (11.4) degree. Knee of BKP were extended significantly narrower. During just before the take-off, the mean pre-projection angles of CM were BKP;- 6.7 (4.4) degree, CON;-8.2 (4.3) degree. BKP was significantly more horizontally. At take-off, projection angles of CM were BKP;-8.2 (5.2) degree, CON;-10.5 (4.9) degree. BKP was more horizontally near and significantly larger. Vertical velocities of CM at the take-off were BKP;- 0.65 (0.45) m/s, CON;-0.81 (0.45) m/s. BKP was near the zero and significantly lager. Other items for the take-off and for flight was not seen significantly difference. DISCUSSION: At the set position, the CM of BKP displaced to anterior. It was in agreement with study of squattingto-standing movement that heel elevation primarily influenced postural adjustment as anterior displacement of the hip.In BKP, the rear knee angle was about 90 degree. Isometric force-angle relationship of knee extension had reported that larger force was at 105 to 120 degree than other degree condition. Therefore, the rear knee of BKP should be more extend a little more. It seemed that the pre-projection angle of BKP approached horizontally was a preferable effect with back plate. There were a few influences of the back plate at take-off and during flight phase. As subjects did not have an enough skill for using a back plate yet, they could not keep the domination on the starting block.